The function of chemical folic acid in calibration methods and neurodevelopmental disorders - Zhou, Ziqi; Wang, Meng; Fan, Qiongli; Zhao, Yan; Wang, Nianrong (Frontiers in Chemistry, 2024)
The functional molecules have been attracted more attentions in environmental or physiological investigates. Especially, the folic acid (FA) could be considered as one key factor in estimating, adjusting, and making decision in the real treatment of neurodevelopmental disorders. It should render the general significance and conceptual for reconsidering molecular science and detections, which gives advancement both in biological structure and detection methods. Among in this application, FA molecule acts as a coenzyme incorporation of carbon atoms as well as in the addition of synthesis purines and pyrimidines. Therefore, the calibration method exhibits the real requirements can be subjected to challenging role as sensing platforms and detecting approaches, which conveys the internal relationship between FA molecule and physiological characterization. In this mini review, it briefly discusses multiple FA applied fields and detection pathways, which could supplement the utilization in relative anticipating the onset of disease.